Effect of seed borne fungi on seed quality of sunflower (Helianthus annuus) - M. MONICA; B. RAJESWARI; K. KESHAVULU; K.V.S. MEENA KUMARI; M. SURESH; R.D. PRASAD (Seed Research, 2026)
An experiment was conducted to study the effect of Alternaria helianthi on seed quality attributes of sunflower (Helianthus annuus L.) cultivars. Alternaria blight infected seeds were thin, pale black, shrivelled, wrinkled, ill filled and showed discolouration on seed coat. Morden and Local cultivars of Ranga Reddy and Nizamabad districts recorded highest total seed-borne fungi (53 and 55%). The samples of Nalgonda district recorded maximum occurrence of seed-borne fungi (49%), whereas occurrence of A. helianthi was recorded with a range of 2.5-4.5%. Significant differences in seed germination (44-60%) and seed vigour index (470-797) was recorded. The germinabilty was far below the minimum seed certification standard of <75% in infected sunflower seed samples. Moisture content in seed samples varied from 6-7%. Seed rot and seedling blight were high in morden cultivar (24 and 15%) and least in Pioneer hybrid of Medak district (10 and 4%). A. helianthi and seed borne fungi present in the sunflower seeds drastically reduced seed quality parameters, viz. germination, seed vigour and oil content, over healthy seed samples.